2017
DOI: 10.1177/1403494817725687
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported school demands and psychosomatic problems among adolescents – changes in the association between 1988 and 2011?

Abstract: Changes in school demands over time could not explain the increasing trend in psychosomatic problems among adolescents. Since the relationship between school demands and psychosomatic problems is strong across time, there is, however, a continued need for school-based interventions. More studies are required to gain further understanding of adolescent mental health from a trend perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
4
12
0
Order By: Relevance
“…In line with earlier findings [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], higher demands were associated with greater perceived stress and an increased risk of recurrent pain. The result that higher levels of demands were associated with a lower morning cortisol response may seem counterintuitive, but align with previous studies reporting that chronic stressors, including exposure to bullying, are linked to lower cortisol levels [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with earlier findings [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], higher demands were associated with greater perceived stress and an increased risk of recurrent pain. The result that higher levels of demands were associated with a lower morning cortisol response may seem counterintuitive, but align with previous studies reporting that chronic stressors, including exposure to bullying, are linked to lower cortisol levels [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…Previous research has shown that many adolescents, particularly girls, report high levels of stress-related health complaints [ 5 , 6 ], with school demands having been identified as one central stressor in the lives of adolescents [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Thus, examining if there are school-based resources that may help students to reduce their experiences of stress is a relevant task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sweden, school demands have increased, according to adolescent self-reports between 1988 and 2011 (Nygren & Hagquist, 2017). An OECD report (2016) stated that, in Sweden, pupils aged 11-15 from lower socioeconomic backgrounds feel more pressure from schoolwork than those from higher socioeconomic backgrounds.…”
Section: School-related Stress Exposure and Mental Health Problemsmentioning
confidence: 99%
“…Classroom disorder is one aspect of classroom climate, a pertinent school‐related factor associated with adolescents' internalizing problems . Research showed that social, learning, and environmental aspects of classroom climate were associated with internalizing problems.…”
mentioning
confidence: 99%